La estimulación temprana para el desarrollo de la motricidad gruesa de los niños de 3 años, de la Unidad Educativa Atahualpa del cantón Ambato, año 2022” - Palacios Rosero, Mirza Diobana (2022)
The evolution of individuals goes through an important stage when the transition from home to the Educational Institution happens, this occurs in access to Initial Education; the skills of the first years of life are revealed in a different environment and without the presence of parents and family. This moment of growth coincides with the consolidation of various elements of which motor skills are taken as the main, for this purpose, the general objective: prepare a didactic guide for the development of gross motor skills of 3-year-old boys and girls from the Atahualpa Educational Unit of the Ambato canton in the year 2022. In order to fulfill the aforementioned purpose, a systematic work is designed based on the postulates of the scientific method and its application in the development of the study. Concomitant with this, a qualitative investigative approach is assumed, the description of the object of study is made and the subject under study is addressed from the founded characteristics and the context of the Institution investigated. It is concluded that the diagnosis of motor skills for the development of gross motor skills of the children under study was relevant, through the perception of the teacher, with support for curricular planning and activities that allow identifying the current situation. ; In the same way, the research variables are based on theory and activities that favor a correct performance of gross motor skills are broken down as a key element in the growth and acquisition of skills with performance criteria